(untitled) (International Journal of Environmental Sciences, 2025)
The parametric study of hexagrid structure has been carried out by analyzing and designing 14 storey real life structure. The parameters nominated for evaluation were 3 different cross sectional shapes i.e., channel section, cold form hat section and buckling restrained brace section.